Pacing behaviour development of swimmers: a longitudinal analysis of the 200m freestyle - Menting, S. G. P.; Post, A. K.; Nijenhuis, B. S.; Koning, R.; Visscher, C.; Hettinga, F. J.; Elferink-Gemser, M. T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Due to the low efficacy of the swimming movement and relatively high resistance of water, pacing is crucial for swimming performance [1]. Cross-sectional studies show that in the 200m freestyle event, adolescent swimmers tend to start too fast, as an even pacing behaviour has been proposed to yield the best performance and is preferred by elite adult swimmers [1,2]. Studies in speed skating have indicated that during adolescence, pacing behaviour develops to better fit the task demands and that an early development of pacing behaviour relates to a higher performance level in adulthood [3]. It is therefore hypothesised that the pacing behaviour of 200m freestyle swimmers will develop towards a more even pacing behaviour during adolescence, and adolescent swimmers of a higher performance level already exhibit a more even pacing behaviour.